Investigating Pragmatic Failure of Iraqi EFL University Students in Academic Writing - Salih, Naseer Tareq; Sahab, Marwan Mizher (Journal of Tikrit University for Humanities, 2025)
This study aims to investigate the pragmatic failure of Iraqi EFL university students in academic writing by addressing three central objectives: to evaluate the overall level of students’ pragmatic competence, to identify the specific types and frequency of pragmatic failure in their academic texts—particularly in the areas of speech acts, politeness strategies, hedging, and implicature—and to determine whether gender plays a significant role in pragmatic performance. The study sample consists of 75 fourth-year undergraduate students from Colleges of Education for Humanities and for Women at Tikrit University, representing a diverse yet academically similar cohort of Iraqi EFL students. To achieve the study’s objectives, a carefully designed diagnostic test is administered, targeting the students’ ability to apply pragmatic principles within academic discourse. The test items are based on real-world academic communication contexts and assessed the appropriateness of pragmatic strategies use by the participants. Statistical analysis of the results, including a one-sample t-test and one-way ANOVA, revealed that the students generally exhibited low levels of pragmatic competence, with the mean scores falling significantly below the expected benchmark. Among the four pragmatic components examined, hedging emerged as the most successfully applied strategy, indicating some awareness of academic tone and tentativeness in claims. In contrast, politeness strategies are the most problematic, suggesting a lack of sensitivity to formality and audience expectations in academic writing. Furthermore, the analysis shows no statistically significant difference between male and female students in terms of their overall pragmatic performance. These findings highlight the pressing need for explicit instruction in academic pragmatics within Iraqi EFL curricula and support the integration of communicative strategies to enhance students’ ability to produce effective, culturally and contextually appropriate academic texts.